Development of method for managing risk factors for emergency situations when using low-sulfur content fuel in marine diesel engines - Sagin, Sergii; Sagin, Arsenii (Technology audit and production reserves, 2023)
The operation process of marine diesel engines when using fuel with a sulfur content of no more than 0.1 % was chosen as the object of the study. Similar types of fuel are characterized by a lower auto-ignition temperature and higher calorific value. During combustion, this leads to an increase in the rate of fuel combustion and the degree of pressure increase during combustion, precisely because of this, the dynamic loads on the parts of the cylinder-piston group and diesel engine bearings increase. Also, this (due to the increase in temperature at the end of combustion) creates conditions for an increase in the concentration of nitrogen oxides in diesel exhaust gases. This (namely, the change in dynamic and thermal loads that occur during the use of fuels with a reduced sulfur content in marine diesel engines) leads to the occurrence of emergency situations. As a method of managing the risk of such emergency situations, the reconfiguration of the high-pressure fuel equipment, namely the change of the advance angles of the fuel supply, is proposed. The research was carried out on a vessel intended for the transportation of containers and on which a marine diesel engine 8K80ME-8.2-TII MAN-Diesel & Turbo was installed as the main engine. Combustion pressure, the degree of pressure increase during combustion, the temperature of exhaust gases, and the concentration of nitrogen oxides in exhaust gases were chosen as the indicators for evaluating the use and implementation of the proposed method. It has been experimentally proven that this results in an increase in the environmental sustainability of diesel operation by 3.61–10.97 %, an increase in thermal stability – up to 2.54 %, and an increase in dynamic stability – up to 4.82 %. This is due to the shift of the self-ignition and combustion process towards expansion and the corresponding decrease in pressure and temperature at the end of combustion. The most favorable use of this method is on modern diesel engines that have an electronic fuel injection control system, so they do not require mechanical reconfiguration of fuel pumps. Taking this into account, the method based on the change of fuel advance angles is defined as the one that provides management of the risk factors of emergency situations when using low-sulfur fuel in marine diesel engines.